Briefe wider die Freidenker: Apologetik und schöne Literatur im 18. Jahrhundert - Spiekermann, Björn (Daphnis, 2022)
Abstract Since the middle of the 18th century, the epistolary form was increasingly used as a means of apologetics. Thereby, theologians reacted to the combination of fiction and philosophy, which gave unexpected success to religious criticism from Britain and France - especially to Voltaire. However, the alliance of apologetics and fine literature had limited viability and only lasted for about a generation. These circumstances will be demonstrated by analyzing Johann H. C. Zahn’s Letters to the Freethinkers (1764-1767) in their wider historical context.
Gesehen am 06.03.2023
Keywords: Aufklärung; Kritik; Voltaire; Freidenker; Apologetik; Brief